The Correlation Between Knowledge With Community Behavior In Antibiotic Use In Kelurahan Petukangan Utara With Home Pharmacy Care - Adin Hakim Kurniawan; Wardiyah Wardiyah; Yuri Tadashi (Politeknik Kesehatan Kemenkes Jakarta II, 2019)
Uncontrolled antibiotics use can induce antibiotics resistance cases. The community believe that antibiotics can cure all disease. Because of that Pharmacist is needed home pharmacy care related by antibiotics use knowledge to justify people's misconceptions. The main purpose of this research to analysis relationship between knowledge of behavior using antibiotics in Kelurahan Petukangan Utara with home pharmacy care. This research is non-experimental with a cross sectional study design. The sample used in this research was the community of Kelurahan Petukangan Utara with cluster random sampling metode is 101 responden by questionnaires. The data analysis used chi-square statistic test. The results showed that there were categories of antibiotic knowledge (55.4%) and antibiotic Behavior (53.5%). There is a significant relationship between knowledge with community behavior antibiotics use with p-value=0.015; OR: 4.979 in Kelurahan Petukangan Utara